Forging Identity : The Story of Carlos Nielbock's Detroit. - Draus, Paul J.; Nielbock, Carlos A. (East Lansing : Michigan State University Press, 2025)
"An urban sociologist befriends a visionary Detroit craftsman, artist, and inventor. Over the course of the next several years Paul Draus records how Carlos Nielbock's life experiences act as a lens that refracts the key challenges facing the city of Detroit and presents the city's redevelopment as an evolving high-stakes drama. Combining sociological context and theory, Draus chronicles Nielbock's mixed-race upbringing in postwar Germany, his journey to find his Black father in 1980s Detroit, his struggles with racial and cultural adversity, and his ambitious artistic vision for Detroit's future. Direct observations, interviews, and historical research on Detroit's ascendance, decline, and resurgence underpin Nielbock's story. The book explores race and identity, craftsmanship and capitalism, and criminal justice and incarceration"--
Intro -- Contents -- Acknowledgments -- A Note on Illustrations -- Introduction -- Chapter 1. Curly Hair, Curly Mind -- Chapter 2. Welcome to Detroit -- Chapter 3. Craftsman and Contrarian -- Chapter 4. Confronted with the Might -- Chapter 5. Crazy as Hell -- Chapter 6. Fighting (For) Detroit's Future -- Conclusion -- Afterword, by Carlos Antonios Nielbock -- Epilogue, Marsha Music -- Farewell to Clarence -- References
Description based upon print version of record.
JSTOR
Keywords: Nielbock, Carlos; Metal-workers -- United States -- Biography; Detroit (Mich.) -- Social conditions -- 20th century; Detroit (Mich.) -- Social conditions -- 21st century; Nielbock, Carlos; Metal-workers--United States--Biography.; Detroit (Mich.)--Biography.; Detroit (Mich.)--Social conditions--20th century; Detroit (Mich.)--Social conditions--21st century; Travailleurs des métaux -- États-Unis -- Biographies; BIOGRAPHY & AUTOBIOGRAPHY / General